Exploring Instructional Technology Trend in during Covid-19 Pandemic: A Systematic Scoping Review - Abdullah, Muhaimin; Sampelolo, Rigel (Universitas Terbuka, 2024)
This scoping review explores the trend of technology use in the teaching and learning of English during Covid-19 pandemic. The materials included in the systematic scoping review were Scopus-indexed research-based articles published in 2021 and 2022 exploring and/or examining technology utilized for the teaching and learning of English during Covid-19 pandemic. The criteria of inclusion applied were (1) Scopus-indexed articles; (2) Research-based publication; (3) published in 2021 and 2022; (4) free- and/or open-access artecle; and (5) focus on the utilization of technology in TEFL during Covid-19 pandemic. In addition, this scoping review also reveals the methodological trend applied by publications in the mentioned years of publication. The result shows that the most popularly utilized technology in TEFL during Covid-19 pandemic are respectively video-conferencing application, website and learning management system (LMS), instant messaging application, social media, and video-sharing platform. In terms of the focus of studies, affective aspect and cognitive aspect become the mostly researched topics. Furthermore, studies on the utilization of technology in TEFL during Covid-19 pandemic are dominated by respectively quantitative studies, qualitative studies, and mixed method. Worldwide practice of teaching English through technology during Covid-19 pandemic is expected to inspire educational practitioners, further researchers, and instructional learning designers and developers about the potential of technologies to be adopted, adapted, and developed for teaching and learning purposes in post-Covid-19 pandemic.